INOVASI BIROKRASI PEMERINTAHAN ANTI KORUPSI BERBASIS TEKNOLOGI INFORMASI DAN KOMUNIKASI (MELIHAT KEBIJAKAN E-PROCUREMENT) - Syauket, Amalia; Poedji Lestari, Sri; P Simarmata, Rajanner (Jurnal Manajemen Publik dan Kebijakan Publik (JMPKP), 2020)
Until the end of 2019, Indonesia's ranking in the anti-corruption institution was still in a stagnant position, it had not moved significantly in its ranking. The ranking is based on the aspect of the ease of investing in a country. Factors that have a significant effect on the high and low rankings of Indonesia are Indonesia's bureaucracy and corruption. Various bureaucratic pathologies have made the bureaucracy ineffective and inefficient in carrying out government functions. Since the reign of President Sukarno to President Joko Widodo, corruption in Indonesia has continued from Sabang to Merauke, therefore the commitment to eradicate corruption in Indonesia is very important .. The manifestation of the Indonesian Government's commitment to eradicating corruption is to make enough laws and regulations in Indonesia, but corruption is still rampant because there are still legal loopholes that corruptors can abuse to get out of legal traps. The Indonesian government has made various efforts to eradicate corruption, one of which is by establishing an Anti-Corruption Agencies. Then in the era of globalization which is characterized by digitalization, the Government has also taken to eradicate corruption, which is getting more massive both from its impact and from its actors. This shows that efforts to eradicate corruption are in line with advances in information technology, especially based on communication technology (e-Gov). This study was conducted qualitatively using a variety of secondary materials in the form of literature and internet sources compiled descriptively, with the aim of increasing new understanding of how to eradicate corruption through electronic government, as a solution to preventing corruption so that Indonesia's competitiveness improves